An overview of fingerprint template protection approaches - Siswanto, Apri; Katuk, Norliza; Ku-Mahamud, Ku Ruhana; Abdul Kadir, Evizal (2017)
One possible attack in the biometric system is the template stored in the database. This attack can cause Biometric template information leakage, thus pose a serious privacy security threat.Most available template protection techniques fail to meet all the desired requirements of practical biometric systems such as diversity, revocability, security, and performance matching accuracy. This paper aims to review the various fingerprint template protection (ftp) approaches that have been proposed by researchers in recent decades. Some of the proposed schemes are standard encryption, biometric cryptosystem, template transformation, hybrid scheme and homomorphic encryption.